Firm Value: Does Corporate Governance and Research & Development Investment Matter? - Cut Sri Murinda; Islahuddin Islahuddin; Nuraini A (Jurnal Reviu Akuntansi dan Keuangan, 2021)
This study aims to examine the factors that affect firm value. This research uses purposive sampling method. The sample of the research is 45 financial companies (128 year-firm observations) listed in Indonesia Stock Exchange for the period of 2017-2019. Multiple regression analysis with unbalanced panel data was applied to analyze the data. A corporate governance index published by Globe and Mail with 4 sub-indices is adopted, namely board composition, shareholding and compensation policies, shareholder rights and disclosure. The results of this study indicate that good corporate governance and research & development investment have no effect on firm value. This explains that the implementation of good corporate governance and firm investment in research & development are not the main information for investors in making investments. However, intellectual capital and enterprise risk management disclosure have effect on firm value. The results can be used as a reference for researchers, especially in the accounting sector related to the development of measuring instruments for good corporate governance.